2009
DOI: 10.3329/bsmmuj.v2i1.3705
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hepatitis C Virus in Bangladeshi General Population

Abstract: Background: Hepatitis C virus is encountered sporadically in Bangladesh. It results in a wide range liver diseases, with asymptomatic acute hepatitis rarely at one end to HCC at the other end of the spectrum. Methods: 1018 individuals of different age groups and sex with varied religious, educational and social backgrounds were tested for anti-HCV by ELISA. Before testing, blood samples were preserved at -20°C. The study was conducted in a semi-urban location on the outskirts of Dhaka. Results: 0.88% tested po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 9 publications
10
91
0
Order By: Relevance
“…In a study HBsAg prevalence among the general population in Bangladesh was reported as 5.5%, which places our country in an intermediate HBV endemicity zone. 22 In Bangladesh representative population study regarding the prevalence of the HCV is lacking. Except for the work by a Japanese group, that reported 5% prevalence of HCV in Bangladesh 26 , others reported extremely low prevalence of HCV in Bangladesh 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study HBsAg prevalence among the general population in Bangladesh was reported as 5.5%, which places our country in an intermediate HBV endemicity zone. 22 In Bangladesh representative population study regarding the prevalence of the HCV is lacking. Except for the work by a Japanese group, that reported 5% prevalence of HCV in Bangladesh 26 , others reported extremely low prevalence of HCV in Bangladesh 27 .…”
Section: Discussionmentioning
confidence: 99%
“…There was a male predominance and those who tested positive were mostly between 17 and 50 years of age. 31 Most of the previous studies regarding HCV prevalence were conducted in different selected groups of people. [32][33][34][35] The prevalence of anti-HCV was reported from high risk groups of Dhaka: 0.8% among truck drivers and helpers 32 ; 0.9% among women at a STD clinic 33 ; 1.6% among women living near a truck stand 34 ; 5.8% in noninjectable drug users (non-IDUs) and 24.8% in IDUs 35 ; and 13% among hepatitis patients 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Four (0.2%) participants were positive for anti-HCV. 30 In another study 31 conducted in a semi-urban location on the outskirts of Dhaka, 1018 individuals of different age groups and sex with varied religious, educational and social backgrounds were tested for anti-HCV by ELISA. Of them 0.88% tested positive for anti HCV; but none of them tested positive for HBsAg.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although there is a paucity of information about a nation-wide survey regarding HBV prevalence in Bangladesh, published data show that about 5%-6% of apparently healthy individuals are HBV carriers in Bangladesh. [4][5][6] In another study the prevalence of HBV infection among the students of a Girls' School of Dhaka city was found to be 2.3%, 7 it was 7% in multi-transfused thalassemic patients 8 and 3.6% in pregnant women of Dhaka city. 9 About 350 million people are chronically infected globally.…”
Section: Introductionmentioning
confidence: 99%
“…11 Identification of risk factors & routes of its transmission will help to prevent global spread of the disease, especially in endemic regions. 12 Boys are affected more than girls, probably due to higher chance of exposure. 13 According to existing reports, there is no seasonal variation for primary HBV infection and it is more common among urban children than that of in rural children.…”
Section: Introductionmentioning
confidence: 99%